Improved visualization of oral microbial consortia- Associated images - Ramirez Puebla, Shamayim Tabita; Mark Welch, Jessica; Borisy, Gary (Zenodo, 2024)
These images are associated to the paper "Improved visualization of oral microbial consortia" published in the Journal of Dental Research. Sample author: Tabita Ramirez Puebla Images show microbial consortia from human tongue dorsum biofilm. Imaged in a confocal microscope (Zeiss LSM 780) with a spectral detector (32 channels). Objective: Plan-Apochromat 63X; N.A. 1.4; Oil Pixel size: 0.07 um x 0.07 um Image size (pixels): 2048 x 2048 Optical section : 1 micron